Detection of residual E. coli and CHOhost-cellDNA in recombinant proteins by qPCR - N. D. Yolshin (Биопрепараты: Профилактика, диагностика, лечение, 2018)
Production of recombinant proteins is a steadily growing industry in Russia and all over the world. Both producer and substance should be properly characterized and tested against all safety criteria. One of the mandatory requirements to the mentioned drugs is the assessment of the content of residual DNA-producing cells, which should be less than 10 ng per dose. There are not many commercial kits for detection of residual DNA and they are based on four different methods. The article provides a brief overview of these methods and highlights their advantages and disadvantages. Common disadvantage of all the commercial kits is their price. The main goal of the research was to choose an optimal method of DNA extraction from protein substances and samples of various protein purification steps, as well as to work over measuring the amount of residual E. coli DNA and CHO by qPCR method not using commercial kits. The article also provides with a number of practical recommendations on specific aspects of DNA extraction and reference standard storage. The aim of the study was to find a reliable and inexpensive method for determining residual DNA-producing cells in recombinant protein samples. The article provides with an overview of DNA extraction methods, stipulates the necessity of DNA extraction prior to the analysis. The advantage was given to the method of spin-column extraction. Optimal DNA extraction method for its assay in a substance is the method, which provides with a stable DNA yield, including different chemical structure of the samples, and upon the condition that no protein and other impurities are detected in the isolated DNA solution. The proposed method for DNA spin-column extraction is the least labor-intensive, is optimized for DNA isolation from protein substances and samples of various protein purification steps. Self preparation of solutions for DNA extraction is a simple procedure and can reduce analysis costs. The report on successful adaptation of the methods of residual E. coli and CHO DNA detection by qPCR using fluorescent probes was provided. The sensitivity of the method was demonstrated at least 1 pg/ml for the analysis of the amount of residual DNA both for E. coli and CHO.